Development of Candidate Reference Materials of Endosulfan Sulfate and Bifenthrin in Black Tea - Nurhani Aryana; Yosi Aristiawan; Dillani Putri; Dyah Styarini (Universitas Gadjah Mada, 2016)
The candidate reference materials of endosulfan sulfate and bifenthrin in black tea have been developed according to the requirements of ISO Guide 34 and 35. Preparation of candidate material includes grinding and sieving of the black tea leaves, spiking the black tea powder by both analytes, homogenization, and bottling. Homogeneity and short-term stability test were performed using a GC-µECD instrument. Meanwhile, the characterization was carried out by a collaborative study using both of GC-µECD and GC-MS instruments. The uncertainty budget was evaluated from sample inhomogeneity, short-term instability and variability in the characterization procedure. In a dry mass fraction, endosulfan sulfate was assigned to be 491 µg kg-1 with a relative expanded uncertainty of ± 33.2%, and bifenthrin was assigned to be 937 µg kg-1 with a relative expanded uncertainty of ± 18.5%. The candidate reference materials are aimed to support the need of matrix CRM especially for the measurement of pesticide residue for quality assurance work done by laboratories in Indonesia.